Self-Reported Physical Activity Level and Associated Factors among Patients with Non-Specific Chronic Low Back Pain - Antoninus Obinna Ezeukwu; Gideon Ebisike; Jeneviv Nene John; Obinna Okezue; Davidson Okwudili John (Shiraz University of Medical Sciences, 2019)
Background: Non-Specific chronic low back pain (NSCLBP) is a common musculoskeletal disorder that leads to impaired physical activity (PA) level and functional limitation, which might cause disability. This study evaluated the self-reported PA level and associated factors among NSCLBP patients. Methods: This cross-sectional study involved 57 patients purposively recruited from the out-patient physiotherapy clinics of two tertiary hospitals. A self-structured questionnaire, long form of International Physical Activity Questionnaire, Roland Morris Disability Questionnaire and Modified Assessing Levels of Physical Activity and fitness (ALPHA) environmental questionnaires were administered to assess the patient's socio- demographic/clinical profile, PA level, disability level and environmental characteristics respectively. Pearson Chi-square and Spearman rank correlation were used to determine the associations between the variables of interest. Alpha level was set at P <0.05. Results: Males had a higher JRPA, TRPA and LTPA. Females had a higher DGPA. Age was significantly negatively moderately correlated with JRPA (P=0.001), TRPA (P=0.016), DGPA (P=0.021) and LTPA (P=0.007). Highest Educational level was significantly positively moderately correlated with JRPA (P=0.001) and LTPA (P=0.002). Pain intensity and disability had a significant negative weak correlation with TRPA (P=0.001) and LTPA (P=0.048), respectively, while sidewalks availability was significantly positively moderately correlated with LTPA (P=0.001). Crime safety at day (P=0.001) and at night (P=0.024) was significantly moderately negatively correlated with LTPA. Conclusion: The PA level of NSCLBP patients was moderate and influenced by socio-demographic, clinical and environmental factors. These factors should be considered in the management of these patients to encourage and promote PA participation.